Chemical constituents and antimicrobial activity of Goniothalamus macrophyllus (Annonaceae) from Pasoh Forest Reserve, Malaysia - Ab Ghani, Siti Humeirah; Mohtar, Mastura; Mohamad Ali, Nor Azah; Jamil, Mailina; J. A., Saiful; Hamid, Muhajir; Abdullah, Mohd Puad (Academic Journals, 2010)
The essential oils from the twig and root of Goniothalamus macrophyllus were obtained by hydrodistillation and subjected to Gas Chromatography (GC-FID) and Gas Chromatography/Mass Spectrometry (GC-MS) using CBP-5 capillary column in order to determine their chemical composition. Both twig and root oils and four reference standard compounds (α-pinene, linalool, geraniol and geranyl acetate) were evaluated for their antimicrobial properties against gram positive and gram negative bacteria, yeast and dermatophyte fungi using broth microdilution methods. The GCMS analysis revealed twenty-one and fourteen compounds from twig and root oils which represented 90.0 and 42.5% of the total oils, respectively. The oils were found to possess the following major components: twig: geranyl acetate (45.5%), geraniol (17.0%), linalool (12.7%) and camphene (7.5%); root: cyperene (9.8%), geranyl acetate (9.4%), geraniol (3.4%) and linalool (2.6%). Other components present in appreciable amounts in both essential oils were α-pinene (0.8%) and benzaldehyde (0.5%). The root oil exhibited the most notable inhibitory activity (0.3 mg/ml) against Vancomycin intermediate-resistance Staphylococcus aureus (VISA 24), Staphylococcus epidermidis and Candida albicans. α-pinene meanwhile inhibited the bacteria and fungal growth at 0.3 and 2.5 mg/ml. With regards to antimicrobial potential, α-pinene superceeds linalool, geraniol and geranyl acetate, respectively.